Risk assessment methodology for Underground Coal Gasification technology. (10th October 2022) - Zagorščak, Renato; Metcalfe, Richard; Limer, Laura; Thomas, Hywel; An, Ni; Bond, Alex; Watson, Sarah
Abstract: Geoenergy technologies, including the Underground Coal Gasification (UCG), are currently being considered as possible solutions for reducing emissions of CO2 and other gases to atmosphere and at the same time, provide sustainable sources of low-carbon energy. In this paper, a flexible risk assessment methodology for UCG technology is presented, based on an established methodology for radioactive waste repositories. The assessment methodology can be applied at any stage in a project, between initial planning and final site abandonment. Central to the approach is the analysis of scenarios, which represents a "source-pathway-receptor" combination and its evolution. Here, a Reference Scenario (RS) and several Alternative Scenarios (AS) are developed and analysed using a numerical model. Results of the RS suggest that contaminant concentrations at an evaluation point are far below any level that could reasonably be detected. In some AS, the calculated concentrations showed an increasing trend at the end of the assessment period, potentially approaching levels that conceivably could be detected. However, as such cases are unexpected and pessimistic, their inclusion is to illustrate worst cases that could happen, rather than to give predictions. An illustrative application demonstrates that plausibly the risks of groundwater contamination from a UCG site should be very low if the site is developed and operated appropriately. The outcomes from applying the numerical model are intended to demonstrate how the methodology and the numerical model can be readily adapted to different sites. Highlights: Flexible risk assessment methodology for UCG technology is developed. Source-pathway-receptor linkage is used to develop a set of scenarios. Reference and Alternative Scenarios are analysed using a numerical model. Risks of groundwater contamination are low, if a site is operated appropriately. Methodology and numerical model can be readily adapted to different sites.